Unraveling the relationship between gut microbiota and site-specific endometriosis: a Mendelian randomization analysis - Tang, Yuanyuan; Yang, Jiangbing; Hang, Fu; Huang, Hui; Jiang, Li (Frontiers in Microbiology, 2024)
Background Although numerous studies have illustrated the connection between gut microbiota and endometriosis, a conspicuous gap exists in research focusing on the pathogenesis of endometriosis at various sites and its linkage with infertility. Methods In this study, we used a two-sample Mendelian randomization analysis to investigate the effect of gut microbiota on the development of endometriosis in different regions, including the uterus, ovary, fallopian tube, pelvic peritoneum, vagina, and rectovaginal septum, as well as the intestine. Additionally, we explored the correlation between gut microbiota and endometriosis-induced infertility. Genetic associations with gut microbes were obtained from genome-wide association study (GWAS) datasets provided by the MiBioGen consortium, whereas endometriosis-related GWAS data were sourced from the FinnGen dataset. In our analysis, single-nucleotide polymorphisms were used as instrumental variables, with the primary estimation of the causal effect performed via the inverse variance weighting method. Our sensitivity analyses incorporated heterogeneity tests, pleiotropy tests, and the leave-one-out method. Results We identified associations at the genus level between four bacterial communities and endometriosis. Subsequently, several associations between the gut microbiota and various subtypes of endometriosis at different anatomical sites were recognized. Specifically, three genera were linked with ovarian endometriosis, six genera were associated with tubal endometriosis, four genera showed links with pelvic peritoneum endometriosis, five genera were connected with vaginal and rectovaginal septum endometriosis, and seven genera demonstrated linkages with intestinal endometriosis. Additionally, one genus was associated with adenomyosis, and three genera exhibited associations with endometriosis-induced infertility. Conclusion Our study elucidates associations between gut microbiota and site-specific endometriosis, thereby augmenting our understanding of the pathophysiology of endometriosis. Moreover, our findings pave the way for potential therapeutic strategies targeting gut microbiota for individuals grappling with endometriosis-related infertility.